From Family to Peer Systems: mixed-Methods Study of Spillover Mechanisms on Juvenile Delinquency in China - Liu, Tzu-Hsuan (Crime & delinquency, 2023)
This article contributes to the field of mixed methods by exemplifying the complementarities of two of the most widely used quantitative and qualitative analytic methods to explore the general pattern of the spillover effects on juvenile delinquency. It employed exploratory sequential and convergent mixed-methods. To ensure validity and reliability of the measurement items, the exploratory sequential mixed research design guided construction of the questionnaire and data collection. Structural equation modeling and fuzzy-set qualitative comparative analyses corroborated the empirical findings. Results from the mixed-methods analyses showed the significance of marital conflict?s spillover effects on juvenile delinquency and recognized the multiple paths through which youth mental health problems and delinquent peer associations operate as key mechanisms connecting marital conflict to juvenile delinquency.